Essential of international and joint R&D projects - Gunasekaran, A. (Technovation)
The role of R&D has been gaining ground in industrial projects, especially with a focus on new product development and technologies and on internationalizing operations that can include manufacturing, projects and service in nature. With the growing importance of technologies such as CAD/CAM and IT in minimizing the time to reach the market, the R&D plays a predominant role in improving the competitiveness of firms. Also, firms in recent years have internationalized operations to improve their overall business performance. The major problems for these firms are how to manage various R&D activities in international operations, and to formulate strategies for improving the effectiveness and quality of international and joint R&D projects. In this paper, an attempt has been made to discuss the management issues of international and joint R&D projects that include : (i) the need for joint R&D projects; (ii) the location of R&D facilities abroad; (iii) the selection of joint and international R&D projects; (iv) evaluating and monitoring joint and international R&D projects; (v) integration between the laboratories, corporate offices and interested divisions within each firm in a joint R&D project; and (vi) managing international and joint R&D projects. Based on the literature survey, this paper presents strategies and methods to manage international R&D projects successfully.